2008
DOI: 10.3201/eid1403.070816
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Eastern Equine Encephalitis Virus, New York

Abstract: Southern strains are undergoing amplification, perpetuation, and overwintering in New York.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 28 publications
5
47
0
Order By: Relevance
“…11,14 To test this hypothesis, published structural gene sequences from 18 EEEV isolates obtained from regions outside Florida were analyzed with structural gene data obtained from the Florida isolates. The sequences from the GenBank isolates included in this analysis are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…11,14 To test this hypothesis, published structural gene sequences from 18 EEEV isolates obtained from regions outside Florida were analyzed with structural gene data obtained from the Florida isolates. The sequences from the GenBank isolates included in this analysis are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Samples from Alabama were collected in 2003 at an EEEV-endemic site located in the Tuskegee National Forest in east central Alabama. 6,[11][12][13][14] Collection details on all isolates used in this study are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Northeastern United States, recent studies have suggested that the virus is periodically introduced from Florida, where it establishes itself in defined foci. [8][9][10][11] The virus then continues to circulate in these foci for several years. However, the mechanism that the virus uses to overwinter in these foci remains obscure.…”
Section: Introductionmentioning
confidence: 99%